Analysis of the Effects of the Implementation of Inclusive Chemistry Education: A Systematic Review - Fauzan Abrori; Dyah Purwaningsih; Muhamad Aditya Hidayah (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
Inclusive chemistry education faces challenges in accommodating the diverse learning needs of students with special needs, particularly in adapting instructional strategies, developing accessible learning media, and implementing equitable assessment practices that support meaningful participation and learning achievement. Therefore, this review aims to map learning strategies, media used, characteristics of students with special needs, and the assessment system in inclusive chemistry education. The method used was a systematic literature review (SLR) following the PRISMA guidelines while, analyzing 15 articles on inclusive chemistry education. The synthesis results indicate that inclusive chemistry instruction requires flexible, multimodal strategies that leverage adaptive technologies such as augmented reality, inclusive videos, audio applications, and virtual laboratories, along with a differentiated approach to reduce learning barriers. The learning media used are diverse and range from 3D tactile models to digital simulations that support more accessible conceptual representations. Research also indicates that students with diverse special needs, including autism, deafness, blindness, low vision, physical impairments, intellectual disabilities, learning disabilities, and neurodivergent conditions, require specific instructional accommodations. Assessment systems vary from pretest–posttest to project-based assessments and affective observations, although; not all studies report comprehensive academic evaluations. Consequently, a broader search method and inclusion of a greater number of journal articles is needed, particularly regarding assessment and evaluation systems in inclusive chemistry education, as current literature remains limited. Additionally, curriculum reviews for students with disabilities have not been extensively discussed and should therefore be a focus of future research